1990
DOI: 10.1289/ehp.9084173
|View full text |Cite
|
Sign up to set email alerts
|

Cotinine analytical workshop report: consideration of analytical methods for determining cotinine in human body fluids as a measure of passive exposure to tobacco smoke.

Abstract: A two-day technical workshop was convened November 10-11, 1986, to discuss analytical approaches for determining trace amounts of cotinine in human body fluids resulting from passive exposure to environmental tobacco smoke (ETS). The workshop, jointly sponsored by the U.S. Environmental Protection Agency and Centers for Disease Control, was attended by scientists with expertise in cotinine analytical methodology and/or conduct of human monitoring studies related to ETS. The workshop format included technical p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(61 citation statements)
references
References 33 publications
1
60
0
Order By: Relevance
“…Among adult nonsmokers exposed to ETS, the half-life of cotinine ranges 1-2 days (7-40 h), and is somewhat longer among children, ranging 32-82 h, and even up to 160 h in neonates [6,56,57]. Cotinine can be measured in plasma, urine and saliva, and the choice of the optimal body fluid is still a controversial question [5,58]. Cotinine can be quantified with a double antibody radioimmunoassay [56], with an enzyme-linked immunosorbent assay [59] or with gas chromatography [58,[60][61][62].…”
Section: Biomarkersmentioning
confidence: 99%
“…Among adult nonsmokers exposed to ETS, the half-life of cotinine ranges 1-2 days (7-40 h), and is somewhat longer among children, ranging 32-82 h, and even up to 160 h in neonates [6,56,57]. Cotinine can be measured in plasma, urine and saliva, and the choice of the optimal body fluid is still a controversial question [5,58]. Cotinine can be quantified with a double antibody radioimmunoassay [56], with an enzyme-linked immunosorbent assay [59] or with gas chromatography [58,[60][61][62].…”
Section: Biomarkersmentioning
confidence: 99%
“…Nicotine, one of the most important components of tobacco, has a plasma life of approximately 30 min (Machacek and Jiang, 1986) and it is quickly converted to its metabolite, cotinine. The latter has been used as a biomarker of tobacco use (Cuff et al, 1989;Watts et al, 1990) and its plasma half-life is longer than that of nicotine, ranging from 10-30 h (Benowitz et al, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, his team proposed GC with nitrogen/phosphorus thermionic detection (GC-NPD) technique for chemical analysis and quantification of cotinine. This declaration was then confirmed by Watts and his fellow scientists in 1990, when they observed that there were no cross reactions that occurred, because the elements (nitrogen and phosphorus) in the cotinine molecule was itself used for detection (Matsumoto et al, 2010;Zuccaro et al, 1997;Watts et al, 1990). However, all the above mentioned methods are generally time consuming because sample extraction is done manually and they are expensive since they require trained expertise and costly reagents for equipment maintenance.…”
Section: Salivary Cotinine Detectionmentioning
confidence: 92%
“…Initially, in the early 1980s RIA techniques were used to detect serum cotinine, but this technique has a 0.3% chance of cross reactivity with other tobacco metabolites producing inaccurate results (Watts et al, 1990;Langone& Van Vunakis, 1987;LangoneGjika& Van Vunakis, 1973). Hence, in 1989 Jacob and his team designed an improved gas chromatographic method for quantification of cotinine.…”
Section: Serum Cotinine Detectionmentioning
confidence: 99%
See 1 more Smart Citation